The chloroplast RNA–binding protein CP29A supports rbcL expression during cold acclimation - Benjamin Lenzen; Florian Rösch; Julia Legen; Hannes Ruwe; Nitin Kachariya; Michael Sattler; Ian Small; Christian Schmitz-Linneweber (Proceedings of the National Academy of Sciences, 2025)
The chloroplast genome encodes key components of the photosynthetic light reaction machinery as well as the large subunit of the enzyme central for carbon fixation, Ribulose-1,5-bisphosphat-carboxylase/-oxygenase (RuBisCo). Its expression is predominantly regulated posttranscriptionally, with nuclear-encoded RNA-binding proteins (RBPs) playing a key role. Mutants of chloroplast gene expression factors often exhibit impaired chloroplast biogenesis, especially in cold conditions. Low temperatures pose a challenge for plants as this leads to electron imbalances and oxidative damage. A well-known response of plants to this problem is to increase the production of RuBisCo and other Calvin Cycle enzymes in the cold, but how this is achieved is unclear. The chloroplast RBP CP29A has been shown to be essential for cold resistance in growing leaf tissue of Arabidopsis thaliana . Here, we examined CP29A–RNA interaction sites at nucleotide resolution. We found that CP29A preferentially binds to the 5′-untranslated region of rbcL , downstream of the binding site of the pentatricopeptide repeat protein MATURATION OF RBCL 1 (MRL1). MRL1 is an RBP known to be necessary for the accumulation of rbcL . In Arabidopsis mutants lacking CP29A, we were unable to observe significant effects on rbcL , possibly due to CP29A’s restricted role in a limited number of cells at the base of leaves. In contrast, CRISPR/Cas9-induced mutants of tobacco NtCP29A exhibit cold-dependent photosynthetic deficiencies throughout the entire leaf blade. This is associated with a parallel reduction in rbcL mRNA and RbcL protein accumulation. Our work indicates that a chloroplast RNA–binding protein contributes to cold acclimation of RbcL production.